A simulation model to evaluate the effect of cooperation between grain merchants in managing GM and non-GM segregation for maize. (January 2015) - Coléno, F.C.; Hannachi, M.
Abstract: GM and non-GM coexistence, as defined by the European commission, defines a product as non-GM if it contains less than 0.9% of GM material. To avoid the risk of mixing GM and non-GM in the supply chain it is recommended to separate the two flows with specialized infrastructure. But doing so it is not possible to separate all the product and it lead to an increase of the cost. Using a simulation model of supply chain management we show that if competing grain merchants cooperate by sharing their infrastructure it is possible to increase the quantity of GM and non-GM separated and to decrease the collection cost. Nevertheless such strategy will increase the transaction cost between competing companies. Highlights: We model the collection chain of GM and non GM maize in European context. We explore the cooperation between competitors to reduce cost and increase value. We show that coopetition is more efficient than competition in the supply chain.